Glucose intolerance, diabetes mellitus and atherosclerosis; prospects for prevention. Issue 609 (July 1976) - Keen, Harry
Abstract : Increased prevalence and incidence of arterial disease has become the major cause of disability and death in diabetics in Western cultures—but is much less common among Japanese and African diabetics. In the West, the presence of lesser, 'subdiabetic' degrees of glucose intolerance are probably independent 'risk factors' for accelerated atherosclerosis. Although many explanations for the link have been advanced—among them direct effects of glucose and insulin on the arterial wall, less direct effects of circulating lipoproteins, abnormalities of blood clotting and fibrinolysis and elevated blood pressure, even the influence of antidiabetic treatment itself—none has been clearly established. Nevertheless there is scope and hope that appropriate measures may reduce the raised arterial disease risk in the diabetic.